ROLL OF LOCAL FLAP TECHNIQUE IN THE MANAGEMENT OF COMPOUND INJURIES OF LEG - SADH, RAGHVENDRA; PAL, VISHNU (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of this study was to study the feasibility of local flaps in management of soft-tissue defects with exposed fracture bone fragments in lower extremity (particularly the leg) due to trauma. Methods: The present study included 20 cases of traumatized lower extremity having a soft-tissue defect and an exposed bone with or without associated fractures. Study was conducted from January 1989 to August 1990. Local flaps provide a reliable single stage procedure for coverage of lower extremity soft-tissue defects. Distant flap provides good coverage but these procedures are long drown out and tedious. Only those cases were selected in which wound was found to be preferably, in the upper 1/3rd, middle 1/3rd and the upper most part of the lower third of the leg due to easy accessibility and placement of the flaps to these area. (As flaps can easily be transposed to these areas). All flaps, that is, Fasciocutaneous, Musculocutaneous, or local Muscle flaps were under taken as a delayed procedure after careful evaluation of traumatized limb, that is, repeated dressing, debridement and control of infection. Results: In this study, stable wound coverage was achieved in all patients. Most of the patients were in the age group of 18 to 42 (55%), of these 90% were male. The longest duration of follow-up was 14 months and shortest was 3 months. Excellent result were obtained in Muscle and Musculocutaneous flaps while good result was obtained in 10% cases of Fasciocutaneous flap. Conclusion: Stable coverage can be achieved by flap techniques using Fasciocutaneous Muscle of Musculocutaneous flaps. Coverage of exposed cartical bones, tendon and major vessels and adequate control of infection can be achieved by Muscle and Musculocutaneous flap in post traumatized limb. Fasciocutaneous flap (Ponten super flap) is very useful in repair of soft-tissue defect asit is a much simpler, easy to design and construct large flaps are safe due to good circulations, requires less time without any functional loss. Post-operative management is simple for both patient and staff.